Do Industrial Agglomeration and Investment Shrink Regional Inequality? - Farida Rahmawati; Fitriani Romziatin (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
An ideal economy that is enhancing the welfare of society is the primary goal of a Nation. However, prosperity and economic development are distributed adequately in each region as well as in East Java. Some regions could develop faster instead of other regions that lead to a disparity between regions in the regency/city of East Java Province. For this reason, this research comprehensively aims to analyse how the impact of industrial agglomeration and regional inequality in East Java. In addition, this study also involves other variables, namely investment and economic growth. The data of the study were obtained from Statistics Indonesia and the Investment Office of East Java during the period 2014 to 2018. The findings indicate that agglomeration provides a key role in inequality in the East Java region. Furthermore, investment has a negative influence on regional inequality, while economic growth positively influences regional inequality in East Java.